Multilayer Structuring of Nonleaded Metal (BiSn)/Polymer/Tungsten Composites for Enhanced γ‐Ray Shielding. Issue 6 (22nd June 2020) - Kim, Hoyeon; Lim, Junyoung; Kim, Jihun; Lee, Jungil; Seo, Yongsok
Abstract : In order to protect from the unrecognized exposures to high‐energy γ ‐rays, Yongsok Seo, and co‐workers, article number 1901448, prepared nonleaded metal (BiSn)/polymer and tungsten (W) composites. A multi‐layer (BiSn / polymer)/W laminate can offer a sufficient thickness with flexibility and an effective shielding against γ ‐rays to be used for protective clothing or equipment.